Importance of ivermectin to human onchocerciasis: past, present, and the future - Cupp, Ed W (Res Rep Trop Med, 2011)
Ivermectin (registered for human use as Mectizan(®)) was donated by Merck & Co Inc in 1987 for the treatment and control of human onchocerciasis (“river blindness”). This philanthropic gesture has had a remarkable effect in reducing the incidence and prevalence of this serious ocular and dermatological disease, while changing health system support for millions of people worldwide. Over 800 million doses have been given to more than 80 million people for onchocerciasis during the past 23 years. As a result, onchocerciasis has been significantly reduced in more than 25 countries, transmission has been interrupted in foci in at least 10 countries, and the disease is no longer seen in children in many formerly endemic foci. Recent communications have suggested that the drug’s efficacy as the major therapeutic agent for these control and elimination programs may be threatened, but alternative interpretations for suboptimal response/resistance suggest otherwise. Current research needs and control methods by which the public health community in endemic countries may respond to resistance, should it occur in their area, are discussed, along with the continuing importance of this anthelmintic as the mainstay in onchocerciasis control programs.